Research Note: Nutrient Evaluation of Compost and Vermicast Produced Through On-site Production Technique - Sinon, Feliciano G.; Atanasio, Mark D. (Annals of Tropical Research, 2014)
This study, evaluates the process flow of nutrient from raw materials to compost to vermi fertilizer, and to assess the possibility of on-site organic fertilizer production technique. Four different types of weeds such as Cogon (Imperata cylindrica), Hantutuknaw (Melastoma malabaticum), Hagunoy (Chromolaena odorata) and Bugang (Saccharum spontaneum) were collected in the project site of Guinsangaan, Inopacan, Leyte. These were shredded (using the mobile Plant Power Shredder) and placed inside a 1 m × 1 m × 1 m black plastic screen (9 mesh per cm2). The materials were allowed to decompose simulating the field condition. A 3/7 parts of chicken manure, 3/7 parts of soil taken from the project area and 1/7 parts of the compost were mixed together inside the screen container (approx. ½ m3 mixture). Three hundred grams of night crawler vermi were placed inside the container with the mixture. Each plastic screen was also placed inside the bin with silk screen (approx 200 mesh) bottom which were laid flat in the shaded and moist area. The temperatures inside the bin ranged from 23 ⁰C to 30 ⁰C which were conducive for the growth of the worms. The Night Crawler thrived and grew in the open field condition — the weight of the stocked worms increased by 3.33% to 16.67%. NPK contents of the vermicast from the different bedding materials were more or less similar, although initially, these were obviously different. Hagonoy composts which was abundant in the marginal uplands was 2.5% higher in N compared to Cogon, Bugang and Hantutuknaw.